ChemInform Abstract: Intercalation‐Driven Reversible Control of Magnetism in Bulk Ferromagnets. Issue 38 (10th September 2014) - Dasgupta, Subho; Das, Bijoy; Knapp, Michael; Brand, Richard. A.; Ehrenberg, Helmut; Kruk, Robert; Hahn, Horst
Abstract Nondestructive intercalation and de‐intercalation of mobile Li ions in γ‐Fe2O3 results in a significant reversible change of the magnetic state of the material.